ANALYSIS OF THE EFFECTIVENESS OF A SOLAR-POWERED PARABOLIC TROUGH WATER FILTRATION SYSTEM (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
Clean water is critical for sustainable development. There has been a growing demand for quality drinking water worldwide. Drinking water is one of the most essential goods for humankind and a necessary element of survival, but also a factor that significantly impacts health. The present study evaluated the effectiveness of a solar-powered parabolic trough water purification system. A parabolic trough with a predetermined rim angle and length was contemplated for this experiment. The system was constructed and evaluated for its efficiency. From the observation of the system, the maximum temperature recorded in the cylindrical parabolic trough with a glass cover was 95ºC, and the maximum temperature recorded in the cylindrical parabolic trough without a glass cover was 66 ºC. The result indicated that the efficiency of the cylindrical parabolic trough with a glass cover was 63.79 percent, whereas the efficiency of the same device without a glass cover was 39.4 percent. This demonstrates that the glass cover served its purpose well in preventing solar insolation from escaping the parabolic trough. No considerable change was found in the pH value of the water after the condensation. The pH value stayed in the range of 7-7.5 throughout the experiment. The finding has implications for sustainable quality water.